The (non) compliance with the brazilian law on inclusion of persons with deficiency in brazilian public concourse (Revista Direito em Debate, 2024)
This study investigated compliance and non-compliance with the necessary biopsychological assessment, carried out by a multidisciplinary and interdisciplinary team, for people with disabilities, as regulated by the Brazilian Law on the Inclusion of Persons with Disabilities, aiming to fill job vacancies in the various administration entities public, always through public competition. The investigation analyzed notices for the opening of competitions, especially investigating the administrative procedures adopted by some public competition boards, as well as the possible losses caused, which victimize an important portion of the Brazilian population.
Keywords: Biopsychological assessment; Deficiency person